Surgical Treatment of Liver Metastases in Neuroendocrine Neoplasms - Palepu Jagannath; Deepak Chhabra; Shailesh Shrikhande; Rajiv Shah (International Journal of Hepatology)
Neuroendocrine neoplasms (NENs) are a distinctive entity, and nearly 10% of patients already have liver metastases at presentation. The management of neuroendocrine liver metastases (NEN-LM) is complex with differing patterns of metastatic presentation. An aggressive approach should be used to resect the primary tumor, to remove regional lymph nodes, and to resect or treat appropriate distant metastases (including liver tumors). Despite having an indolent course, NENs have a significantly reduced survival when liver metastases are untreated. Though a wide range of therapies are now available with a multimodal approach to the treatment, surgical treatment offers the only chance for a significant survival prolongation and/or improvement of symptoms and quality of life. A review of the existing surgical modalities for NEN-LM is discussed in this paper.